2015
DOI: 10.1007/s12035-015-9474-x
|View full text |Cite
|
Sign up to set email alerts
|

BDNF in Lower Brain Parts Modifies Auditory Fiber Activity to Gain Fidelity but Increases the Risk for Generation of Central Noise After Injury

Abstract: For all sensory organs, the establishment of spatial and temporal cortical resolution is assumed to be initiated by the first sensory experience and a BDNF-dependent increase in intracortical inhibition. To address the potential of cortical BDNF for sound processing, we used mice with a conditional deletion of BDNF in which Cre expression was under the control of the Pax2 or TrkC promoter. BDNF deletion profiles between these mice differ in the organ of Corti (BDNFPax2-KO) versus the auditory cortex and hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 80 publications
(122 reference statements)
4
55
0
Order By: Relevance
“…ABR to click and pure tone stimuli and the cubic 2*f1-f2 DPOAE for f2=1.24*f1 and L2=L1-10 dB were recorded in adult 1-to 8-month-old anesthetized mice. From click-evoked ABRs, consecutive wave components that reflect the summed neural activity along the ascending auditory pathway were analyzed as described [31][32][33]. In vivo electrocochleography (compound action potentials of the auditory nerve, CAP; summating potential of IHC receptor potentials, SP; receptor potential of OHCs, cochlear microphonic, CM) was performed in anesthetized mice as described [34].…”
Section: Hearing Testsmentioning
confidence: 99%
“…ABR to click and pure tone stimuli and the cubic 2*f1-f2 DPOAE for f2=1.24*f1 and L2=L1-10 dB were recorded in adult 1-to 8-month-old anesthetized mice. From click-evoked ABRs, consecutive wave components that reflect the summed neural activity along the ascending auditory pathway were analyzed as described [31][32][33]. In vivo electrocochleography (compound action potentials of the auditory nerve, CAP; summating potential of IHC receptor potentials, SP; receptor potential of OHCs, cochlear microphonic, CM) was performed in anesthetized mice as described [34].…”
Section: Hearing Testsmentioning
confidence: 99%
“…In conclusion, an increasing number of studies have now demonstrated that the counting of IHC ribbons after hearing loss, for example, in aged specimens [62,64] , or after an acoustic trauma [22,31,32,61,75,76] , or after intake of aminoglycoside [77,78] , can be a first indication of the loss of IHC synapses and AN integrity, independent of (elevated) hearing thresholds.…”
Section: Molecular Biomarker For Dissection Of the Ihc Phenotype And mentioning
confidence: 91%
“…The resulting pressure waves from the motion of the epithelium, triggered by the active OHC process, are conducted (backwards) through the middle ear to the eardrum, which moves like a loudspeaker diaphragm to produce a sound pressure wave, which can be measured in the ear canal [26] . For technical details of DPOAE measurements in rodents, see [21,22,[30][31][32][33] .…”
Section: Dpoae As a Functional Biomarker To Detect Ohc Functionmentioning
confidence: 99%
See 2 more Smart Citations